2020
DOI: 10.3390/pr8101219
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterization of Home-Made Soap from Waste-Used Frying Oils

Abstract: The study aimed to describe the utilization of waste frying oils, originated mainly from households, in home-made soap production and to emphasize the advantages of soap biodegradation in comparison to biological treatment of oils. The physicochemical analyses of soaps were used to check the differences between the samples made of fresh and fried oils. Significant (p < 0.05) difference between the soaps made of fresh/fried olive oil pair was obtained, while the rapeseed sample pair did not differ significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
(52 reference statements)
0
14
0
2
Order By: Relevance
“…Most natural soaps create no toxic waste and byproducts and require a minimal amount of energy in the production process; thus, they are more compatible with nature ( Maotsela et al, 2019 ). Small manufacturers and households can easily produce natural soaps with simple and accessible ingredients ( Antonić et al, 2020 ).…”
Section: Common Ingredients Of Soapmentioning
confidence: 99%
“…Most natural soaps create no toxic waste and byproducts and require a minimal amount of energy in the production process; thus, they are more compatible with nature ( Maotsela et al, 2019 ). Small manufacturers and households can easily produce natural soaps with simple and accessible ingredients ( Antonić et al, 2020 ).…”
Section: Common Ingredients Of Soapmentioning
confidence: 99%
“…Soap samples from rapeseed oil had higher MDA values for the samples R0 and R1 (2.09 and 2.58 µg/g, respectively) than for the samples made from fried oil with a higher TPM. The reason might be found in some reactions during and after the saponification process that have still not been studied [13]. Soap samples made from sunflower oil had values ranging from 4.46 (S1) to 6.61 µg/g (S5).…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…By some studies, soaps degrade up to 4 times faster than oils. This is mainly due to their higher accessibility to microorganisms [12,13]. In addition, supportive data come from the studies that include saponification as the one step in waste frying oil-rich wastewater treatment [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dordevic’s teams developed the utilization of waste frying oils in home-made soap production. The results indicated that soaps produced from fried plant oils represent acceptable products from economic and environmental points of view [ 13 ]. Tremlova et al also found out the obtained results did not show exact differences between experimentally produced soap samples from fried or unfried oils [ 14 ]…”
Section: Introductionmentioning
confidence: 99%